CONCEPTUAL METAPHOR OF DEPRESSION IN KOREA ESSAY BOOKS 죽고 싶지만 떡볶이는 먹고 싶어 (JUKKKO SIPJJIMAN TTOKPPOKKINEUN MOKKO SIPO) ‘I WANT TO DIE BUT I WANT TO EAT TTEOKBOKKI’: COGNITIVE SEMANTIC STUDY: METAFORA KONSEPTUAL DEPRESI DALAM BUKU ESSAI KOREA 죽고 싶지만 떡볶이는 먹고 싶어 (JUKKKO SIPJJIMAN TTOKPPOKKINEUN MOKKO SIPO) ‘AKU INGIN MATI TAPI AKU INGIN MAKAN TTEOKBOKKI’: KAJIAN SEMANTIK KOGNITIF - Ni Gusti Ayu Dhyana Widyadewi; Cece Sobarna; Elvi Citraresmana (LLDIKTI Wilayah X, 2023)
The widespread use of metaphors in medical therapy dialogues and the heightened mental health issue in South Korea made researchers want to study further how the unique forms of metaphors are produced, one of which is depression. This study aims to find out what conceptualizations of depressive metaphors are produced in mental health therapy dialogs between the writer and his psychiatrist which are described in the Korean essay book 죽고 싶지만 떡볶이는 먹고 싶어 (Jukkko Sipjjiman Ttokppokkineun Mokko Sipo) 'I Want to Die But I Want to Eat Tteokbokki ' by Baek Se-Hee with a study of cognitive semantics. This study uses a descriptive qualitative approach with the method of collecting data using listening and note taking techniques. The data analysis method used in this study is Metaphor Identification Procedure Vrije Universiteit (MIPVU) procedure. Data presentation methods used are formal and informal methods. As a result, there are four conceptual metaphors of depression that are formed, namely DEPRESSION IS A PRISON, DEPRESSION IS A SPINNING WHEEL, DEPRESSION IS DARKNESS, and DEPRESSION IS WAR. These four conceptualizations are formed from various metaphorical expressions expressed by the author and his psychiatrist regarding the depression experienced by the writer.